Essays on imperfect banking competition and macroprudential policy - Melo, Matheus Anthony de (2022)
This thesis consists of two essays. This first chapter evaluates the role of financial frictions and imperfect banking competition in the Brazilian business cycle. We estimate a dynamic stochastic general equilibrium (DSGE) model that incorporates a Cournot banking sector where banks accumulate capital subject to a capital adequacy requirement. Our findings show that the spread is more significant in scenarios with imperfect banking competition and bank capital adequacy requirements. The amplified countercyclical spread, which arises from the interaction of the imperfect banking competition and bank stress channels, tends to amplify the response of output, consumption, and other macroeconomic variables to adverse shocks. We show that most of the spread increase in Brazil is due to financial shocks, especially after 2008. The second chapter studies the stabilization properties of time-varying capital requirements in an environment dominated by an oligopolistic banking sector that accumulates capital subject to a leverage adequacy cost. Our results indicate that the macroprudential policy can stabilize fluctuations in Brazil's business and credit cycles by controlling the loan rate and, consequently, affecting the spread in the banking system. A welfare analysis shows that welfare gains from the introduction of macroprudential policy depend on the type of shock that hits the economy, and more banking competition can amplify the benefits of macroprudential policy. The results still highlight those time-varying capital requirements should not be a substitute for monetary policy but a helpful complement to deal with financial problems or adverse sectoral shocks.